Learning from home during pandemic: A blended learning for reading to write activity in EFL setting - Setyowati, Lestari; Sukmawan, Sony; El-Sulukkiyah, Ana Ahsana (Universitas Muhammadiyah Sidoarjo, 2021)
The pandemic of COVID 19 has forced teachers all around the world to be adaptable to the situation. Within the foreign language (FL) context, the teaching of language skills provides challenges for teachers in terms of how to deliver the materials as effectively and as efficiently as possible. The study aims to describe the steps of reading to write activity for essay writing in FL settings and what the students feel about it. The design of the study is a case study design. The subjects of the study were the fourth-semester students of English Education Study Program, Faculty of Pedagogy and Psychology in Universitas PGRI Wiranegara, Pasuruan, East Java, Indonesia in the academic year 2019-2020. The result of the study shows that there are three main steps of teaching scenarios. They are the pre-activity, whilst activity, and post-activity, with some specifications depending on the skills. The reading section employes the silent reading activity, skimming, and scanning technique through telegram application. The writing section implements the process approach, namely planning, drafting, and revising, and publishing. The technologies used were Telegram, Whatsup, Google Meet, YouTube, Grammarly, and Plagiarism checker online application.